Application and Maintenance of Hydraulic Drive Systems in Sherritt’s Concentrators - L. H. Smith; D. S. Taylor (Canadian Institute of Mining, Metallurgy and Petroleum, 1977)
"AbstractSherritt has been applying hydraulic drives to concentrator equipment since 1967. The initial application was made on a bank of 5- by 5-in. slurry pumps. This has now been extended to all slurry pumps requiring less than 40 hp and several conveyors which require variable-speed or low-speed/high-torque characteristics. The pump motors are directly connected through a flexible coupling, whereas the conveyor systems are directly mounted onto the head-pulley shaft extension.The different applications and design concepts will be described, with outlines of the operating and maintenance advantages and disadvantages and costs. The paper also outlines future possible applications, together with the limiting conditions, of such systems.IntroductionSHERRITT GORDON MINES LIMITED has been operating a mining division in Northern Manitoba for almost 50 years. The original mining operation was at Sherridon, Manitoba and was a copper-zinc producer. This mine was exhausted in 1948 and the mining plant was moved north to its present location at Lynn Lake, Manitoba. The Lynn Lake Mine is a nickel-copper producer. Since 1960, two new mines have been discovered and brought into production in the general vicinity of Lynn Lake. The first of these was the Fox Mine, a copper-zinc property operating at 3,000 tons per day from an underground operation. This mine started production in May 1970."